2009
DOI: 10.1007/s11468-009-9110-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Optimization, and Characterization of SERS Sensor Substrates Based on Two-Dimensional Structures of Gold Colloid

Abstract: International audienceGenerally, the immobilization of two-dimensional nanoparticles in immersion procedures is time-consuming (over 24 h). In this paper, we report a very effective and simple method to fabricate two-dimensional gold nanoparticle patterns over large areas with high regularity for surface-enhanced Raman scattering (SERS). We achieved a highly sensitive SERS colloid surface by optimizing temperature and immersion time. The surfaces were characterized by X-ray photoelectron spectroscopy, UV-Vis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…In the present study, V ranging between 1.9 and 2.3 kV was used for electrospraying. The dispersion of SERS nanoparticles and their interaction with analyte molecules determine the enhancement behavior (Ko et al, 2008;Oh et al, 2009;Addison and Brolo, 2006;Makiabadi et al, 2010;Sun et al, 2011). Therefore, Ag nanoparticles in the suspension, in the gas phase and deposited on the substrate were characterized.…”
Section: Characterization Of the Electrospray Systemmentioning
confidence: 99%
“…In the present study, V ranging between 1.9 and 2.3 kV was used for electrospraying. The dispersion of SERS nanoparticles and their interaction with analyte molecules determine the enhancement behavior (Ko et al, 2008;Oh et al, 2009;Addison and Brolo, 2006;Makiabadi et al, 2010;Sun et al, 2011). Therefore, Ag nanoparticles in the suspension, in the gas phase and deposited on the substrate were characterized.…”
Section: Characterization Of the Electrospray Systemmentioning
confidence: 99%
“…The adsorption spectra show a single maximum at 520 nm in aqueous medium. This absorption band results when the incident photon frequency is resonant with the collective oscillation of the conduction band electrons and is known as the SPR [30,31]. Figure 3a(b-d) shows the extinction spectra of substrates after the immobilization of nanoparticles for different soaking times (3,30, and 60 min) in the colloidal solution of AuNPs.…”
Section: Resultsmentioning
confidence: 99%
“…A colloidal solution is obtained from a mixture of chloroauric acid solution (HAuCl 4 ) and a trisodium citrate solution (Na 3 C 6 H 5 O 7 ) [11]. A Dynamic Light Scattering (DLS) experiment revealed that the diameter of the nanoparticules was about 15 nm.…”
Section: Tip-probe Preparationmentioning
confidence: 99%
“…Note that the intensity of the electromagnetic field strongly depends on the nanoparticle size, shape, and interparticle distance. Such high enhancement factors are also obtained from well-defined nanostructures, like nanoparticles [9][10][11], nanoholes [12] or nanotips [13]. Hence, Tip-Enhanced Raman Spectroscope (TERS) [14][15][16][17][18][19] exploits this effect induced by a nanotip, derived from the local probe microscopy techniques, among the Atomic Force Microscopy (AFM) is the most notorious example.…”
Section: Introductionmentioning
confidence: 99%